Effects of mulching, terracing, and efficient irrigation on soil salinity reduction in Uzbekistan’s Fergana Valley - Mirzohid Koriyev; Ismoiljon Mirzahmedov; Karimjon Boymirzaev; Zuhriddin Juraev (Cogent Food & Agriculture)
This study investigates the effects of mulching, terracing and efficient irrigation methods on soil salinity and agricultural sustainability in the Fergana Valley, Uzbekistan. We focus on a semi-arid region and investigate how integrated soil management techniques can mitigate soil degradation while improving crop productivity and water efficiency. Over a 10-year period, we have conducted field experiments to quantify changes in soil salinity, moisture retention and crop yields. The results show that organic mulching significantly lowers soil salinity and stabilizes soil moisture, while terracing reduces runoff and erosion on slopes. Efficient irrigation methods, especially the use of low mineralization water, also helped to control salinity and improve water use efficiency. The combined application of these practices led to a significant improvement in soil health and fertility, demonstrating their effectiveness in promoting sustainable agricultural practices. These results emphasize the need for integrated soil management strategies to combat soil salinization and support sustainable agriculture in drylands.